2016
DOI: 10.1080/19443994.2015.1035500
|View full text |Cite
|
Sign up to set email alerts
|

CCD series no. 18: record low energy in closed-circuit desalination of Ocean seawater with nanoH2O elements without ERD

Abstract: A B S T R A C TExperimental trials of seawater desalination under closed-circuit desalination conditions are described with a unit comprising four modules, each of four Qfx-SW-400-ES nanoH2O elements, with seawater feed in the cited (parentheses) ranges of salinity (33,801-37,197 ppm), flux (9.2-13.4 lmh), recovery (42-53%), and temperature (15.0-18.4˚C). The normalized results of this study revealed specific energies in the range of 1.453-1.775 kWh/m 3 and permeates in the range of 379-682 ppm. The lowest ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The number of pressure vessels is essentially doubled to allow storage of fresh feed during a cycle (for energy recovery as described in Section 2), but with the benefit of not requiring explicit ERDs. Since the simulated energetics in this study are similar to what has already been reported [27,29], semi-batch RO may be a cost-effective yet energy-saving process design in SWRO desalination.…”
Section: Capital Costssupporting
confidence: 79%
See 1 more Smart Citation
“…The number of pressure vessels is essentially doubled to allow storage of fresh feed during a cycle (for energy recovery as described in Section 2), but with the benefit of not requiring explicit ERDs. Since the simulated energetics in this study are similar to what has already been reported [27,29], semi-batch RO may be a cost-effective yet energy-saving process design in SWRO desalination.…”
Section: Capital Costssupporting
confidence: 79%
“…Although semi-batch RO technically does not need ERDs to recover energy, for SWRO applications an external pressure vessel is typically used as an isobaric work exchanger, similar in working principle to the DWEER and PX Pressure Exchanger devices [27,29]. During the concentration cycle, the vessel is filled with fresh feed using a low-pressure pump.…”
Section: Batch and Semi-batch Reverse Osmosismentioning
confidence: 99%
“…There are desalination technologies that have demonstrated lower energy intensities at lab-scale than the SOA cited here. One of these is semi-batch RO [69,70]. Gal & Efraty reported an energy intensity for semi-batch RO of 1.48 kWh e /m 3 for a 556 m 3 /day capacity unit operating at 42% recovery, 3.6% feedwater salinity, 0.38% product water salinity and a pressure of 4850 KPa [69].…”
Section: Concentrate Managementmentioning
confidence: 99%
“…One of these is semi-batch RO [69,70]. Gal & Efraty reported an energy intensity for semi-batch RO of 1.48 kWh e /m 3 for a 556 m 3 /day capacity unit operating at 42% recovery, 3.6% feedwater salinity, 0.38% product water salinity and a pressure of 4850 KPa [69]. Results from modeling show that fully-batch RO may be able to operate at even lower energy intensities, but this has not been demonstrated at physical-scale to the best of the authors' knowledge [71,72].…”
Section: Concentrate Managementmentioning
confidence: 99%
“…For example, the implementation of CCD to treat 35 000 mg L −1 seawater reported a low SEC of 1.9–2.2 kWh m −3 without ERD, but the obtained permeate has relatively high TDS of 379–682 mg L −1 . [ 136 ]…”
Section: Strategies For Energy Reduction In Desalination Processesmentioning
confidence: 99%